INSTITUTIONAL CHALLENGES AND LAW ENFORCEMENT IN THE REGULATION OF CRYPTO-ASSETS - Abdukokhor Abdivaitovich Iminokhunov; Abdurakhmon Muhammad-Ali ugli Khakimov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the institutional challenges of regulation and law enforcement in the circulation of crypto-assets. It is established that the key constraint on regulatory effectiveness is institutional uncertainty, driven by the absence of unified criteria for the interpretation of legal categories. Contradictions in law enforcement practice are identified, and the relationship between conceptual uncertainty and the asymmetry of legal risks is substantiated. Conceptual models of the formation of institutional uncertainty and law enforcement in the crypto-asset domain are proposed. An approach to ensuring consistency in law enforcement is developed.